Analysis of Microbial Diversity in Soil under Ginger Cultivation. (23rd October 2017) - Liu, Yiqing; Wu, Lin; Wu, Xingwen; Li, Honghai; Liao, Qinhong; Zhang, Xiaojing; Sun, Zhiqiang; Li, Wenhua
Abstract : Ginger is a perennial monocotyledonous herb, which can be used as both a vegetable and a medicinal plant. However, it is susceptible to various plant pathogens. Microbial diversity in soil is related closely to the health and productivity of plant crops including ginger. In the current study, we compared microbial diversity from soil samples under ginger cultivation (disease incidence of >50% [relatively unhealthy sample] versus disease incidence of <10% [relatively healthy sample]). The bacterial and fungal taxa were analyzed by Illumina-based sequencing, with 16S and ITS identification, respectively. Both bacterial and fungal OTUs were significantly more in the healthy soil sample than the unhealthy sample. Moreover, the dominant bacterial and fungal genera were detected to be different in each sample. Rhodanobacter and Kaistobacter were the dominant bacterial genera in the healthy sample, while Rhodoplanes and Bradyrhizobium were the dominant genera in the unhealthy sample. For fungal analysis, Cladosporium, Cryptococcus, and Tetracladium were the dominant genera in the healthy sample, while Lecanicillium, Pochonia, and Rhodotorula were the dominant genera in the unhealthy sample. Collectively, the basic information of microbial diversity in ginger soil is helpful for elucidating the ginger-microbe interactions and potentially selecting suitable plant growth-promoting rhizobacteria and biocontrol agents for ginger production.